Clinical Features of Embolic Stroke of Undetermined Source - Wang, Weijing; Tang, Xiaomei; Liu, Wei; Jia, Ke; Zhao, Xingquan; Yu, Fengchun (Frontiers in Neurology, 2020)
Abstract Background and objective：one-third of ischemic stroke have no identifiable cause after standard evaluation. In 2014, researchers have proposed the concept of Embolic Stroke of Undetermined Source (ESUS). The purpose of this study was to report the clinical characteristics of ESUS and its difference from cardiogenic embolism (CE), large-artery atherosclerosis (LA) and small-artery occlusion lacunar (SA). Methods：Acute ischemic stroke(AIS) patients admitted to the department of Beijing Haidian Hospital from January 2017 to December 2017 were prospectively and consecutively enrolled. Base-line characteristics were collected. Stroke etiologies were presented and compared. We compared the clinical features and infarct sites of patients with acute cerebral infarction of different etiologies. Results：A total of 119 AIS patients were analyzed in the study. There were 33(27.73%) cases in ESUS group, 11(9.24%) cases in CE group, 45(37.82%) cases in LAA group and 30(25.21%) cases in SA group. There were significant differences between the ESUS group and the CE group in the NIHSS score[3 (1.5-5) vs 6 (2-20) , p=0.007], Modified Rankin Score[19, (57.58) vs 9, (81.82), p=0.008], hemorrhagic transformation[0, (0) vs5,(45.45),p<0.001], and left atrial diameter[37.09±3.16vs41.73±5.00, p=0.001]. ESUS group and LA group have different mRS scores[19, (57.58) vs42, (93.33), p<0.001]. ESUS group and SA group have different mRS scores[19, (57.58) vs 28, (93.33), p=0.001]. During one year follow-up, there were 5 cases (15.15%) in ESUS group, 3 cases (27.27%) in CE group 3 cases (6.67%) in LA group and 1 case(3.33%) in SA group with ischemic stroke (cerebral infarction or transient ischemic attack). Conclusion：ESUS is more similar to atherosclerotic cerebral infarction in clinical features, but the distribution of lesions is more similar to cardiogenic embolism, suggesting that the pathogenesis of ESUS needs to be further explored. Key Words：Embolic Stroke of Undetermined Source, Acute ischemic stroke, prolonged heart-rhythm monitoring